Glenn Seaborg and Jackie Kennedy
Black and white photograph of Glenn T. Seaborg (1912-1999) shaking the hand of First Lady, Jackie Kennedy (1929-1994).
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Onassis, Jacqueline Kennedy, 1929-1994